Exploring nurses’ experiences in palliative care: a qualitative study in Indonesia - Jathu Dwi Wahyuni; Setyowati Setyowati; Krisna Yetti; Dewi Gayatri; Ati Surya Meidiawati; Nurdahlia Nurdahlia (Palliative Medicine in Practice)
BACKGROUND: Providing services to palliative patients with a chronic or terminal illness is a moral obligation. Moreover, palliative care is a patient’s right that must be provided by health workers and the community. Unfortunately, the implementation of palliative care services shows that most nurses still have insufficient knowledge and attitudes about palliative care. This study aims to explore the experiences of inpatient cancer and chemotherapy ward nurses in caring for palliative patients. METHODS: This study employed a qualitative descriptive interpretive method and involved 11 participants from March to July 2022. The research subjects were inpatient cancer and chemotherapy ward nurses who cared for palliative patients or those with experience in treating palliative patients. Data were collected using focus group discussions (FGD) and analyzed using content analysis techniques. RESULTS: This study identified three themes: nurses’ perceptions of palliative care, the obstacles experienced by nurses in palliative care, and nurses’ perceptions of solutions to the barriers experienced in palliative care. CONCLUSIONS: This research recommends intervention models for palliative patient management to develop and change nurses’ attitudes, making them more caring and sincere when treating palliative patients.